2022
DOI: 10.1186/s12933-022-01580-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diabetes on mortality and ICD therapies in ICD recipients: a systematic review and meta-analysis of 162,780 patients

Abstract: Background The influence of diabetes on the mortality and risk of implantable cardioverter defibrillator (ICD) therapies is still controversial, and a comprehensive assessment is lacking. We performed this systematic review and meta-analysis to address this controversy. Methods We systematically searched the PubMed, Embase, Web of Science and Cochrane Library databases to collect relevant literature. Fixed and random effects models were used to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…A pooled analysis of chronic kidney disease (CKD) patients who underwent CRT implantation from the MADIT-CRT and RAID trial showed that the patients with more advanced CKD experienced a high non-arrhythmic mortality rate and a lower rate of ventricular arrhythmias, and did not appear to attain the same degree of benefit from a primary prevention ICD [ 77 ]. A retrospective analysis of 3535 diabetic patients in the EU-CERT-ICD registry [ 78 ] and a large meta-analysis of 162,780 patients, comparing diabetic and non-diabetic patients with ICDs [ 79 ], suggested that, as a group, they received attenuated or no benefit from prophylactic ICDs. Prospective randomized data in these groups of patients are lacking.…”
Section: Risk Vs Benefit Of Icdsmentioning
confidence: 99%
“…A pooled analysis of chronic kidney disease (CKD) patients who underwent CRT implantation from the MADIT-CRT and RAID trial showed that the patients with more advanced CKD experienced a high non-arrhythmic mortality rate and a lower rate of ventricular arrhythmias, and did not appear to attain the same degree of benefit from a primary prevention ICD [ 77 ]. A retrospective analysis of 3535 diabetic patients in the EU-CERT-ICD registry [ 78 ] and a large meta-analysis of 162,780 patients, comparing diabetic and non-diabetic patients with ICDs [ 79 ], suggested that, as a group, they received attenuated or no benefit from prophylactic ICDs. Prospective randomized data in these groups of patients are lacking.…”
Section: Risk Vs Benefit Of Icdsmentioning
confidence: 99%
“…Heart failure (HF) is a complex multifaceted syndrome of organic heart disease that occurs in the end stage. 1 It is a significant health care concern, affecting an estimated 30-50 million patients worldwide. 2 Importantly, cognitive impairment (CI) is a commonly co-occurring chronic condition among patients with HF, often accompanied by memory impairment, slower information processing, and impaired executive function.…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure (HF) is a complex multifaceted syndrome of organic heart disease that occurs in the end stage 1 . It is a significant health care concern, affecting an estimated 30–50 million patients worldwide 2 .…”
Section: Introductionmentioning
confidence: 99%